Strategi Meredakan Sentimen Negatif Surat Keberatan Eiger di Media Sosial; Pendekatan Content Analysis - Dessy Kushardiyanti (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2021)
This study aims to determine how the strategy to reduce the negative sentiment of Eiger's objection letter. This study was analyzed based on the theory of image recovery with descriptive qualitative observation methods, namely analyzing the content of Eiger's Instagram and Twitter posts and the content of followers' comments. The results of this study indicate that Eiger implements an image restoration strategy through social media in order to change public perceptions and attitudes, namely to quickly and accurately respond to apologies through the content of